THE APPLICATION OF NON-ROUTINE STRUCTURAL PATTERNS TO OPTIMISE A VERTICAL STRUCTURE (DIMENSI: Journal of Architecture and Built Environment, 2011)
This paper presents the application of non-routine structural patterns as the pattern of the vertical buildings’ perimeter structure to increase the structural performance of the structure. Realising the limitations of the orthogonal pattern, and the current trends to use non-routine patterns, the optimality of three non-routine patterns found in nature and recent building designs are examined. Medium and high-rise buildings are taken as the case studies to observe distinct behaviour of the patterns under different loading condition. Best solutions from distinct patterns are produced by utilising CAD modelling and structural design and optimisation software. Multi-criteria decision making framework is then used to evaluate the performance of the solutions in terms of efficiency, economy, expressiveness and environmental sustainability. The result shows that among the three patterns examined, the triangular pattern can produce optimum structures.